2016
DOI: 10.14260/jemds/2016/220
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors and Developmental Outcome Among Babies With Perinatal Asphyxia in a Tertiary Care Centre

Abstract: BACKGROUNDBirth asphyxia is commonest cause of preventable cerebral injury. It is also important cause of neonatal mortality. Incidence of birth asphyxia however is higher in developing countries and leading cause of neonatal mortality. This work is undertaken to study the incidence, risk factors and outcome of birth asphyxia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2020
2020

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
0
1
0
Order By: Relevance
“…In the study by Reddy et al, risk factors predisposing to perinatal hypoxia were found to be poor antenatal care (24%) and meconium-stained liquor (20%). The study proved that both ante and intrapartum factors are important in causing perinatal hypoxia [26]. Babu et al also observed a statistically significant association with meconium being associated with 42% cases of HIE and p<0.0001 [24].…”
Section: Vol 7 | Issue 2 | February 2020mentioning
confidence: 85%
“…In the study by Reddy et al, risk factors predisposing to perinatal hypoxia were found to be poor antenatal care (24%) and meconium-stained liquor (20%). The study proved that both ante and intrapartum factors are important in causing perinatal hypoxia [26]. Babu et al also observed a statistically significant association with meconium being associated with 42% cases of HIE and p<0.0001 [24].…”
Section: Vol 7 | Issue 2 | February 2020mentioning
confidence: 85%